An easy way to create duration variables in binary cross-sectional time-series data. (December 2020) - Philips, Andrew Q.
In cross-sectional time-series data with a dichotomous dependent variable, failing to account for duration dependence when it exists can lead to faulty inferences. A common solution is to include duration dummies, polynomials, or splines to proxy for duration dependence. Because creating these is not easy for the common practitioner, I introduce a new command, mkduration, that is a straightforward way to generate a duration variable for binary cross-sectional time-series data in Stata.mkduration can handle various forms of missing data and allows the duration variable to easily be turned into common parametric and nonparametric approximations.